Hubungan Pengetahuan Mahasiswi Dengan Tindakan SADARI Dalam Upaya Deteksi Dini Kanker Payudara Di STAI Syekh H.Abdul Halim Hasan Al Ishlahiyah Binjai - Leny Suarni (Universitas Prima Indonesia, 2020)
Breast cancer is a disease in which malignant (cancer) cells are detected in breast tissue, and is a disease that is feared by women. The Medical Record Data of RSUD Dr. RM Djoelham Binjai in 2016 there were 20 cases from the age of 19-21 years 3 people (15%), and aged 30-65 years 17 people (85%). But in reality, women's awareness of doing breast self-examination is still low, due to lack of knowledge and lack of information about the benefits and ways to do breast self-examination. The purpose of this study is to identify the relationship between student knowledge with BSE action in the early detection of breast cancer. . The population of all Sharia banking students in semester IV at STAI Sheikh H. Abdul Halim Hasan Al Ishlahiyah Binjai, amounted to 146 respondents, the number of samples 32 with purposive sampling techniques. Analyze data with Product Moment. The results of the study of the knowledge of the majority of respondents have less knowledge as many as 14 people (44%) and the majority of respondents' BSE measures are not good as many as 17 people (53%). With the value of t table distributed with α = 0.05. Obtained t table = 2.042, the calculated r value = 0.846, with a significant level of 5% the value of r table is 0.349. The results of this calculation indicate that the calculated r value (0.846)> r table (0.349), so that the alternative hypothesis is accepted. Conclusion: There is a Relationship between Student Knowledge and BSE Actions in the Early Detection of Breast Cancer at STAI Sheikh H. Abdul Halim Hasan Al Ishlahiyah. It is recommended that the Institution collaborate with health workers in increasing the knowledge of female students and BSE actions in the early detection of breast cancer.